A Video-Enhanced, Electronic Modality for Preparticipation Examination of Young Athletes. Issue 9 (September 2021) - Parizher, Gary; Phelan, Dermot M.; Ayers, Colby; Goodwin, Russell; Levine, Benjamin D.
Abstract : Abstract: We developed a video-enhanced preparticipation evaluation symptom questionnaire (the V-PPE), intended to help screen athletes for heart disease. We now report results of a pilot quality improvement study evaluating V-PPE's performance. In a prospective before-and-after study, approximately 5700 high-school athletes were prompted to voluntarily fill out the V-PPE questionnaire. We compared symptom frequencies on standard PPE to those on V-PPE. Of 5700 athletes, 46 (0.8%), 117 (2.0%), 33 (0.6%), and 101 (1.8%) reported syncope, angina, palpitations, and dyspnea, respectively on routine screening. Four hundred and ninety-two (8.6%) voluntarily filled out the V-PPE. Athletes were more likely to report palpitations on V-PPE than PPE, but not angina, dyspnea, syncope, or at least one symptom. Symptom frequencies on electronic PPE questionnaires are lower than recent reports suggest. Embedded videos can alter screening yield. More research is necessary to evaluate the predictive value of the V-PPE for clinically relevant cardiac pathology.